Rapid morphological change of nonnative frugivores on the Hawaiian island of O'ahu*. (29th April 2019) - Gleditsch, Jason M.; Sperry, Jinelle H.
Abstract: Novel ecosystems have become widespread created, in part, by the global spread of species. The nonnative species in these environments can be under intense evolutionary pressures that cause rapid morphological change, which can then influence species interactions. In Hawaii, much of the native frugivore community is extinct, replaced by nonnative bird species. Here, we determined if the passerine species of the nonnative frugivore community on O'ahu have morphologically diverged from their native ranges. We compared a variety of traits, all important for frugivory, between museum specimens from the species' native ranges to wild individuals from O'ahu. All four species tested exhibited significant divergence ranging in magnitude from 2.3% to 13.0% difference in at least two traits. Using a method developed from quantitative genetics, we found evidence that a mixture of nonadaptive and adaptive processes worked in concert to create the observed patterns of divergence. Our results suggest that rapid morphological change is occurring and, based on the traits measured, that these changes may influence seed dispersal effectiveness. As these species are largely responsible for seed dispersal on the island, the rapid morphological change of these species can influence the stability and maintenance of plant communities on O'ahu.